Problems and Prospects Towards Implementing Ubiquitous Computing - Abubakar, Mohammed; Ume, Arthur U. (Richtmann Publishing, 2012)
Ubiquitous Computing means network connectivity everywhere, linking devices and systems as tiny as adrawing pin and as large as a worldwide product distribution chain. This paper explores issues arising withimplementing Ubiquitous computing, and gives examples of success stories where researchers leveragedUbiquitous computing effectively. The paper further enumerates certain key issues and factors that affectthe implementation of Ubiquitous computing, and finally provides insights towards how to seamlesslyachieve the adoption of this new era approach to computing.